2008
DOI: 10.1152/jn.01100.2007
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Tactile Stimulation in Deep Cerebellar Nucleus Neurons Result From Recurrent Activation in Multiple Pathways

Abstract: Rowland NC, Jaeger D. Responses to tactile stimulation in deep cerebellar nucleus neurons result from recurrent activation in multiple pathways. J Neurophysiol 99: 704 -717, 2008. First published December 12, 2007; doi:10.1152/jn.01100.2007. In a previous study, we found that neurons in the deep cerebellar nuclei (DCN) respond to 5-ms brief facial tactile stimulation in rats anesthetized with ketaminexylazine with multiphasic response patterns lasting over 200 ms. It remained unclear, however, to what extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 54 publications
6
51
0
Order By: Relevance
“…Our results showing synaptic evoked rebounds in spontaneously firing DCNs are consistent with previous data obtained from more hyperpolarized levels [2][3][4][5], as well as from in vivo recordings [20], and support the idea that rebound excitation is used to transfer inhibitory signals to The stimulus intensity (in microamperes) is indicated for each trace. B Plots of average and maximal frequency, estimated over 1 s after the occurrence of the first spike after the IPSP, versus stimulus strength for the same neuron.…”
Section: Rebound Responsessupporting
confidence: 92%
“…Our results showing synaptic evoked rebounds in spontaneously firing DCNs are consistent with previous data obtained from more hyperpolarized levels [2][3][4][5], as well as from in vivo recordings [20], and support the idea that rebound excitation is used to transfer inhibitory signals to The stimulus intensity (in microamperes) is indicated for each trace. B Plots of average and maximal frequency, estimated over 1 s after the occurrence of the first spike after the IPSP, versus stimulus strength for the same neuron.…”
Section: Rebound Responsessupporting
confidence: 92%
“…Whole-cell recordings in vivo showed that, whereas the increased firing frequency is accompanied by true rebound depolarizations, the timed-spiking activity occurs predominantly before these depolarizations. Despite the effectiveness of the train stimuli applied to the cerebellar cortex, we found the strongest increases in firing frequency when we directly stimulated the IO (41,49,53). Moreover, we found spontaneous rebound firing in CN neurons following hyperpolarizations that have temporal characteristics that are compatible with those of complex spike activities.…”
Section: Discussionmentioning
confidence: 60%
“…1,4,5,[8][9][10]12,13 Some evidence exists for the generation of rebound-like bursts in vivo following periods of reduced firing of DCN cells (including presumed Purkinje cellevoked inhibition) or rebound responses in motor control. [17][18][19][20][21] Yet the potential for intrinsic membrane properties of the type assessed in vitro to generate rebound bursts in response to Purkinje cell inhibitory input has not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%